Olfactory Deficits in the Freezing of Gait Phenotype of Parkinson's Disease - Glover, Aliyah; Pillai, Lakshmi; Dhall, Rohit; Virmani, Tuhin (Frontiers in Neurology, 2021)
Background: Olfactory dysfunction often occurs before motor onset in Parkinson’s disease (PD) and can be detected with the University of Pennsylvania Smell Identification Test (UPSIT). Based on the Braak hypothesis, the olfactory bulb is one of two sites where disease pathology may start and spread to deeper brain structures. Objective: To evaluate whether a specific pattern of odorant identification on the UPSIT discriminated Parkinson’s disease patients with and without freezing of gait. Methods: One hundred and twenty four consecutive participants (33 controls, 31 non-freezers and 60 freezers) were administered the UPSIT. Using the chi-square test, each odorant on the UPSIT was ranked based on the differential ability of freezers and non-freezers to identify them correctly. Using predictive statistics and confusion matrices, the best combination of odorants and a cut-off score was determined. Results: Freezers had a shift towards a more severe hyposmia classification based on age and sex based normative values. The correct identification of 9 odors (bubblegum, chocolate, smoke, wintergreen, paint thinner, orange, strawberry, grass and peanut) was significantly worse in freezers compared to non-freezers. Correctly identifying ≤2 out of 3-odorants (bubblegum, chocolate, smoke) had a 77% sensitivity and 61% specificity for categorizing freezers. The 3-odorant score was not correlated with disease duration, motor or total UPDRS scores, MoCA scores or age at testing. The predictive statistics were similar when sexes were separately categorized. Conclusions: A 3-odorant score helped categorize freezers and non-freezers with similar sensitivity and specificity to short odorant Parkinson’s disease identification batteries.